Effect of Soaking Time of Bamboo Shoot and Concentrations of Lime Paste on Quality of Bamboo Shoot Chips - Herda Hervina; Rahmat Afrizal; Fadlan Hidayat (Serambi Journal of Agricultural Technology, 2019)
The aim of this reserch are to deteremine the effect of lime paste concentration and time soaking, to determine the best condition of making bamboo shoot chips. The resuls of analysis were  processed by using Completely Randomized Design factorial with two repeatation. The lowest water content obtained at the condition of concentration of lime paste of 3% (K2) dan time soaking (L1) of 15 minutes is 4,03. While, the lowest ash content obtained at the concentration of lime  paste (K3) of 5% dan soaking time (L3) of 25 minutes is 3,63.  The best organoleptic of taste was obtained at  concentration of lime paste (K3) of 5% and soaking time (L3) of 25 minutes that was 6,80. The best organoleptic of  flavour was obtained at  concentration of lime paste (K2) of 3% and soaking time (L2) of 20 minutes that was 6,07. While, the best organoleptic of  texture was obtained at  concentration of lime paste (K3 and K2) of 3%  and 5% and soaking time (L1) of 15 minutes that was 3,04.